Factors Related to the Implementation of X-Ray Radiation Safety Management in the Radiology Unit in East Kalimantan, Indonesia - Almas, Sri Warsuni; Peristiowati, Yuly; Wardani, Ratna (Journal of Health Policy and Management, 2023)
Background: The hospital is a complex public health service and a research center for medicine. The wider the function of a hospital, the more complex the equipment and facilities available. One of the specialist supporting medical services in hospitals is radiology using X-ray machines. The use of diagnostic radiology X-rays in Indonesia continues to grow. The aim of the study was to determine the factors that influence the implementation of X-ray radiation safety management in the Radiology Work Unit of the Province of East Kalimantan. Subjects and Method: An observational study with a cross-sectional design was conducted in Radiology Working Unit, East Kalimantan Province in October 2022. A total of 173 respondents were selected using proportional random sampling. The dependent variable is the implementation of X-ray radiation safety management. The independent variables are man, money, method, material and machine. The data were collected using a questionnaire, and analyzed using a linear regression test. Results: Man (b= 0.49; p<0.001), money (b= 0.20; p= 0.007), method (b= 0.47; p<0.001), material (b= 0.23; p= 0.002), and machine (b= 0.11; p= 0.050) have effects on the implementation of X-ray radiation safety management in radiology work units. Conclusion: Man, money, method, material, and machine significantly influence the implementation of X-ray radiation safety management in radiology work units.   Keywords: management, X-ray radiation safety.   Correspondence: Sri Warsuni Almas. Masters Program of Public Health, Strada Institute of Health Sciences, Indonesia. Jl. Manila No.37, Tosaren, Kec. Pesantren, Kota Kediri, Jawa Timur 64123. Email: sriwarsuni99@gmail.com. Mobile: +62 822-5455-3137.